(untitled) (Web of Teachers: Inderscience Research, 2024)
These days, the way the educational process is organized uses a variety of techniques to assess learning outcomes, including written test papers (independent work), control papers, oral questioning, laboratory and practical work, testing, etc. The primary objective of these techniques is to evaluate a student’s knowledge, skills, and talents in a specific field. Outside of the university, students’ intellectual, personal, and “socially significant” accomplishments are not included in the assessment framework. In this sense, assessing the activities of those involved in the educational process requires the use of various techniques and technology. The electronic portfolio technology is one way to assess performance.